IMPLEMENTASI KEBIJAKAN PENERBITAN SURAT PERINTAH MEMBAYAR (SPM) KEUANGAN APBN PADA DINAS PENDIDIKAN DAN KEBUDAYAAN PROVINSI SULAWESI TENGAH - Nurnaila, Nurnaila (Katalogis, 2018)
Payment Order Issuance Policy is one of the State financial management policies to increase awareness of the use of budgets originating from the State Budget, and is a document issued, used by Budget Users, power of Budget User Officials signing the Payment Order to disburse fund allocation, the source of which is from DIPA or other equivalent documents. The research objective was to analyze the implementation of Payment Order issuance policy sourced from the State Budget (Regulation of the Minister of Finance of the Republic of Indonesia Number 250/PMK.05/2010). Type of the research was descriptive qualitative. Data collection was done through observation, interviews, and documentation. The theory used Rippley and Franklin's policy implementation model theory, because Rippley and Franklin's implementation model emphasizes the content of policy aspect. According to Rippley and Franklin, the success of program policy implementation is viewed from three factors; a) compliance perspective that measures the implementation of the compliance of the implementing apparatus; b) The success of implementation is measured by the smooth running of the routine and the absence of problems, and c) successful implementation leads to satisfactory performance for all parties, especially the program beneficiaries. The results show that the implementation of the Payment Order issuance policy for State Budget finance at the Education and Culture Office of Central Sulawesi Province has been carried out well.